Perempuan dalam Novel Renata Karya Hayatur Rahmi (Kajian Feminisme) - Sri Wahyuni; Achmad Wahidy; Yessi Fitriani (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2022)
This study aims to describe the study of feminism in the novel Renata by Hayatur Rahmi. The research method used is a qualitative descriptive method. Data and data sources in the form of words, phrases, and sentences contained in the conversational dialogue on the data source. The source of the data used is in the form of a novel. The data collection technique used technical documentation, namely documents about literature, literary works and feminism studies. The results of the study describe the oppression of female characters, namely: 1) Marginalization, namely in the form of impoverishment of Renata who is prohibited from working because she is considered weak and easily tired. 2) Subordination, in the form of lowering self-esteem towards Renata. 3) Stereotypes in the form of labeling badminton, cheap, bitch towards Renata. 4) Violence, in the form of slaps, threats, yells at Renata, and 5) Workload. The increasing attention to women, especially violence that occurs in Indonesia is the reason why it is important that this research must be carried out, so it can be seen that it is not only in fictional concepts but in the real environment.